Cartilage repair using trypsin enzymatic pretreatment combined with growth-factor functionalized self-assembling peptide hydrogel - Zanotto, Gustavo Miranda, author; Frisbie, David D., advisor; Grodzinsky, Alan, committee member; McIlwraith, C. Wayne, committee member; Barrett, Myra F., committee member; Puttlitz, Christian, committee member (Colorado State University. Libraries, 2019)
Treatment of cartilage defects remains challenging in the orthopedic field. Several techniques are currently available to treat cartilage defects, with subchondral bone microfracture being the most commonly used marrow stimulation technique. However, despite satisfactory results in the short-term, clinical and functional outcomes of microfracture treated patients tend to decline over time. Improving microfracture technique using tissue engineering principles may be a more attractive way to treat cartilage defects compared to other more complex and expensive alternatives. Self-assembling peptide hydrogel has been extensively studied as a scaffold for cartilage repair. This hydrogel is biocompatible within the joint environment and has been shown to increase cartilage healing and improve clinical and functional outcomes in both rabbit and equine models of cartilage repair. Recently, a clinically applicable technique was described using trypsin enzymatic pretreatment of the surrounding cartilage combined with local delivery of heparin binding insulin growth factor-1 (HB-IGF-1). The results of this study demonstrated improved cartilage integration in vitro when this technique is utilized. Thus, in the present study we evaluated the combination of trypsin enzymatic pretreatment with a self-assembling peptide hydrogel functionalized with growth factors to improve cartilage repair. First, the effect of trypsin enzymatic pretreatment alone or combined with self-assembling peptide hydrogel functionalized with HB-IGF-1 and/or platelet-derived growth factor- BB (PDGF-BB) was tested using a rabbit model (48 rabbits). Subsequently, trypsin enzymatic pretreatment combined with self-assembling peptide hydrogel functionalized with HB-IGF-1 and PDGF-BB was used to augment microfracture augmentation in an equine model of cartilage defects (8 horses). In the small animal model, trypsin enzymatic pre-treatment resulted in an overall increase in defect filling, as well as improvements in subchondral bone reconstitution, surface regularity, cartilage firmness, reparative tissue color, cell morphology and chondrocyte clustering. The presence of PDGF-BB alone improved subchondral bone reconstitution and basal integration, while the combination of HB-IGF-1 and PDGF-BB resulted in an overall improvement in tissue and cell morphology. In the equine model, microfracture augmentation using trypsin enzymatic pretreatment combine with self-assembling peptide hydrogel functionalized with growth factors (HB-IGF-1 and PDGF-BB) resulted in better functional outcomes, better defect healing on second look arthroscopy at 12 months, as well as improved reparative tissue histology and increased biomechanical proprieties of the adjacent cartilage compared to defects treated with microfracture only. In conclusion, trypsin enzymatic pretreatment combined with self-assembling peptide hydrogel functionalized with growth factors (HB-IGF-1 and PDGF-BB) resulted in successful microfracture augmentation. These therapeutic approaches can result in a more cost effective way to improve cartilage healing in patients undergoing subchondral bone microfracture.